Kajian Literatur Sistematis Terhadap Aplikasi Mobile Verifikasi Produk Halal: Analisis Metode, Fitur, dan Potensi Inovasi - Rasyadi, M Javier; Kurniawardhani, Arrie (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The rapid growth of the global halal industry has intensified the demand for efficient, transparent, and easily accessible halal product verification methods. This research aims to identify and analyze the commonly used verification methods in halal mobile applications and to evaluate their core and additional features available publicly on the Google Play Store. Using a systematic literature review combined with content analysis of eleven selected mobile applications, this study provides a comprehensive overview of the current digital halal application ecosystem. The findings of this research indicate that barcode scanning is the most dominant method due to its efficiency and ease of use. However, this method has limitations in providing transparent product ingredient details, necessitating support from Optical Character Recognition (OCR) technology for deeper ingredient analysis. A hybrid approach combining barcode, OCR, and manual input was found to be the most optimal, providing application flexibility and resilience across various usage scenarios. Furthermore, regarding application features, this study discovered that additional functionalities such as scan history, fatwa references, user reporting, and ingredient translation remain underutilized, despite being crucial for enhancing user trust and halal literacy. This research provides essential implications for application developers, users, and regulators toward establishing an inclusive and trustworthy halal digital ecosystem.